Draft Annual Plan 2001-2002 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 2001)
Regarding Externally Aided Projects Outlay by Head of Development for District Plan, Centrally Sponsored Scheme Evaluation Studies Financial Outlay and Physical Target, Proposal for New Scheme Agricultural Research Education Agricultural Financial Instruction Special Programme for Rural Development Village and Small Industries General Economic Service Draft Annual Plan 2001-2002.
Government of Pondicherry
Planning and Research Department
Keywords: Proposed Outlay; Physical Target and Achievement; Proposed for Spillover and Ongoing Programme; Maximizing of Completed Programme; Regarding Externally Aided Projects; Outlay by Head of Development for District Plan; Centrally Sponsored Scheme; Evaluation Studies; Financial Outlay and Physical Target; Proposal for New Scheme